Rodent gene drives for conservation: opportunities and data needs. Issue 1914 (6th November 2019) - Godwin, John; Serr, Megan; Barnhill-Dilling, S. Kathleen; Blondel, Dimitri V.; Brown, Peter R.; Campbell, Karl; Delborne, Jason; Lloyd, Alun L.; Oh, Kevin P.; Prowse, Thomas A. A.; Saah, Royden; Thomas, Paul
Abstract : Invasive rodents impact biodiversity, human health and food security worldwide. The biodiversity impacts are particularly significant on islands, which are the primary sites of vertebrate extinctions and where we are reaching the limits of current control technologies. Gene drives may represent an effective approach to this challenge, but knowledge gaps remain in a number of areas. This paper is focused on what is currently known about natural and developing synthetic gene drive systems in mice, some key areas where key knowledge gaps exist, findings in a variety of disciplines relevant to those gaps and a brief consideration of how engagement at the regulatory, stakeholder and community levels can accompany and contribute to this effort. Our primary species focus is the house mouse, Mus musculus, as a genetic model system that is also an important invasive pest. Our primary application focus is the development of gene drive systems intended to reduce reproduction and potentially eliminate invasive rodents from islands. Gene drive technologies in rodents have the potential to produce significant benefits for biodiversity conservation, human health and food security. A broad-based, multidisciplinary approach is necessary to assess this potential in a transparent, effective and responsible manner.